A study on the stimulation and guidance of intrinsic motivation among engineering college students in China - Yang, Kunyue; Han, Dong (Frontiers in Education, 2026)
BackgroundAgainst the backdrop of rapid advancements in artificial intelligence and information technology, engineering university students face complex learning challenges. However, existing tools for measuring their intrinsic motivation—a crucial driver of learning—often lack cultural adaptability in the Chinese context, and systematic intervention strategies are scarce.MethodsBased on Self-Determination Theory and the Intrinsic Motivation Inventory, we developed and locally adapted the Chinese College Student’s Intrinsic Motivation Learning Questionnaire (CIMLQ), removing the less applicable “Relatedness” dimension. The final 30-item instrument covers six dimensions: Interest/Enjoyment, Perceived Competence, Effort, Pressure/Tension, Perceived Choice, and Value/Usefulness. Its reliability and validity were tested with 450 engineering students. Subsequently, a 19-week randomized controlled trial (N = 600) was conducted, comparing an experimental group receiving multidimensional motivation strategies (e.g., goal contracting, choice provision) with a control group under conventional instruction.ResultsExploratory and confirmatory factor analyses demonstrated good structural validity (cumulative variance explained: 66.13%) and internal consistency (Cronbach’s α = 0.829–0.891). The teaching experiment revealed that the experimental group showed a significantly higher post-intervention intrinsic motivation score (119.20 vs. 97.81, *p* < 0.001, a 21.8% increase) and better academic performance (80.10 vs. 76.57, *p* = 0.001) compared to the control group.ConclusionThe CIMLQ proves to be a reliable and valid measure for assessing intrinsic motivation among Chinese engineering students. The findings provide empirical evidence that structured instructional interventions, designed based on the CIMLQ dimensions, can effectively enhance both intrinsic motivation and academic outcomes. This study offers a practical framework for fostering self-directed learning capabilities that are essential for adapting to evolving educational environments.